The determinants of the disclosure of corporate social responsibilities in Malaysia - Abdul Wahid Mohd Kassim; Raman Noordin; Junainah Jaidi; Sulaiman Tahajuddin (Faculty of Business, Economics and Accountancy Universiti Malaysia Sabah, 2024)
This study examines the link between Female CEO, Family Director, Executive Director and ISO 14000 and the quantity of CSR in annual reports. Using content analysis and annual reports from Bursa Malaysia public listed companies, the findings of this study show that from the four variables, only three variables, Family Director, Executive Director and ISO 14000 are associated with the extent of CSRD. The other predictive variable, Female CEO, however, were found to be insignificant.